Propyl Gallate, a Strong Antioxidant, Increases the Ca2+ Sensitivity of Cardiac Myofilament - Naoto Tadano; Sachio Morimoto; Fumi Takahashi-Yanaga; Yoshikazu Miwa; Iwao Ohtsuki; Toshiyuki Sasaguri (Elsevier, 2009)
Ca2+ sensitizers are cardiotonic agents that directly increase the Ca2+ sensitivity of cardiac myofilament. To find a novel Ca2+ sensitizer, we have screened a group of phenolic compounds by examining their effects on the Ca2+-dependent force generation in cardiac muscle fibers. We found that propyl gallate, a strong antioxidant, increased the Ca2+ sensitivity of cardiac myofilament in a dose-dependent and reversible manner. The present study indicates that propyl gallate is a novel type of Ca2+ sensitizer with antioxidant activity, which might be more beneficial for the treatment of congestive heart failure associated with oxidative stress than existing Ca2+ sensitizers. Keywords:: propyl gallate, Ca2+ sensitizer, antioxidant